2014
DOI: 10.1111/tid.12171
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of donor‐derived pulmonary tuberculosis in lung transplant recipients and review of 12 previously reported cases: opportunities for early diagnosis and prevention

Abstract: Validated screening protocols, including microbiological testing and newer technologies (e.g., interferon-gamma release assays) to identify unrecognized M. tuberculosis infection in deceased donors, are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…In our study, TST positivity was not found to be a risk factor for TB. It is also known that lung grafts may be the focus of LTBI . In 1 of our cases, a bilateral‐lung transplant recipient, onset of TB occurred in the early post‐transplant period, thus suggesting that it developed from a donor LTBI.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, TST positivity was not found to be a risk factor for TB. It is also known that lung grafts may be the focus of LTBI . In 1 of our cases, a bilateral‐lung transplant recipient, onset of TB occurred in the early post‐transplant period, thus suggesting that it developed from a donor LTBI.…”
Section: Discussionmentioning
confidence: 68%
“…Through December 2016, a total of 22 case reports, 2 case series and 1 cohort reported on 36 cases of proven (n = 17), probable (n = 8), and possible (n = 11) DDTB cases among 16 lung, 13 kidney, 6 liver, and 1 heart recipient.…”
Section: Resultsmentioning
confidence: 99%
“…Five donors had no identifiable or documented TB risk factors . Donor risk factors for TB were identified retrospectively in 7 cases …”
Section: Resultsmentioning
confidence: 99%
“…Despite these drawbacks, IGRAs may have value as adjunct diagnostic tool in certain clinical situations. As an example, given the increased risk of mycobacterial infection in lung transplant recipients (1,4,38), IGRAs may be used in lung donors with risk factors for prior exposure. In addition, due to increasing migration, diversity among organ donors increases, which should raise awareness for mycobacterial infections even in low-incidence countries (39).…”
Section: Discussionmentioning
confidence: 99%